IMAGE ENCRYPTION USING COMBINATION OF CHAOTIC SYSTEM - Sari, Festy Winda; Ibrahim, Ummi Aisha (Politeknik Negeri Batam, 2024)
These days, image encryption relies on chaos-based theory. Encrypting and decrypting images using random sequences is becoming increasingly popular. Accordingly, this study proposes a method of image encryption based on the Logistic Map and Lorenz System. The encryption and decryption process involves permutation and substitution steps. A permutation is performed using the Logistic Map, which is used for leading randomness of pixels through confusion, while the diffusion process is finished using the Lorenz System. Afterwards, the substitution is performed by bitwise-XORing the value. Throughout the permutation process, the value of the original image's red, green, and blue (RGB) channels will be swapped amongst each and then sent to the next stage, i.e., diffusion. The diffusion process involves changing the values of pixels of the original image. The disturbance in plain images will increase when pixel and bit levels are changed, usually called cypher images. A study will evaluate the effectiveness of chaos-based security and the time cost of key processes. Furthermore, we will investigate the relationship between contiguous pixels.